The global burden of diarrhoeal disease, as estimated from studies published between 1992 and 2000 - Kosek Margaret; Bern Caryn; Guerrant Richard L. (The World Health Organization, 2003)
Current estimates of the global burden of disease for diarrhoea are reported and compared with previous estimates made using data collected in 1954-79 and 1980-89. A structured literature review was used to identify studies that characterized morbidity rates by prospective surveillance of stable populations and studies that characterized mortality attributable to diarrhoea through active surveillance. For children under 5 years of age in developing areas and countries, there was a median of 3.2 episodes of diarrhoea per child-year. This indicated little change from previously described incidences. Estimates of mortality revealed that 4.9 children per 1000 per year in these areas and countries died as a result of diarrhoeal illness in the first 5 years of life, a decline from the previous estimates of 13.6 and 5.6 per 1000 per year. The decrease was most pronounced in children aged under 1 year. Despite improving trends in mortality rates, diarrhoea accounted for a median of 21% of all deaths of children aged under 5 years in these areas and countries, being responsible for 2.5 million deaths per year. There has not been a concurrent decrease in morbidity rates attributable to diarrhoea. As population growth is focused in the poorest areas, the total morbidity component of the disease burden is greater than previously.